Interactive effect of phenylalanine with duration of diabetes on the risk of small vessel disease in Chinese patients with T2DM - Zheng, Jun; Zhang, Wei; Miao, Yu-Yang; Li, Xue-Rui; Luo, Wei-Ming; Yang, Xi-Lin; Fang, Zhong-Ze; Zhang, Qiang (Frontiers in Endocrinology, 2025)
Aims: Few prior studies have explored the relationship between phenylalanine and diabetic small vessel disease (SVD) in different duration of Type 2 diabetes mellitus（T2DM）. Our study aimed to explore whether phenylalanine is associated with the risk of SVD and to further explore whether phenylalanine interacted with duration of T2DM to alter the risk of SVD. Materials and methods: A total of 1032 T2DM patients were derived from Liaoning Medical University First Affiliated Hospital (LMUFAH) system. SVD was defined as patients with diabetic nephropathy (DN) or diabetic retinopathy (DR) alone, or both. Serum amino acids were measured by mass spectrometry (MS) technology. Binary logistic regression model was performed to examine associations of phenylalanine with SVD risk. Restricted cubic spline (RCS) was used to draw odds ratio curves of plasma phenylalanine for SVD. Additive interaction analysis was employed to test interactions of low phenylalanine with long duration of T2DM for SVD. Results: Among 1032 T2DM patients, 286 (27.7%) had SVD. Phenylalanine<42 μmol/L was associated with markedly increased risk of SVD (OR 1.76, 95%CI 1.23 to 2.51), which was enhanced by≥5 years of duration of T2DM to 4.83 (95%CI 2.97-7.87) with significant additive interactions. Inclusion of phenylalanine and duration of T2DM into a traditional risk factor model substantially increased the area under ROC curve from 0.67 to 0.71 (95% CI 0.70 to 0.75) (P <0.05). Conclusions: In Chinese patients with T2DM, phenylalanine<42μmol/L was associated with increased risk of SVD, which was further amplified by ≥5 years of duration of T2DM.